2017
DOI: 10.1002/ece3.3267
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability of soil respiration in a seasonal tropical forest

Abstract: We monitored soil CO 2 effluxes for over 3 years in a seasonally wet tropical forest in Central Panama using automated and manual measurements from 2013 to 2016. The measurements displayed a high degree of spatial and temporal variability. Temporal variability could be largely explained by surface soil water dynamics over a broad range of temporal scales. Soil moisture was responsible for seasonal cycles, diurnal cycles, intraseasonal variability such as rain‐induced pulses following dry spells, as well as sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 79 publications
8
51
1
8
Order By: Relevance
“…For example, tropical moist forests, such as our site, might exhibit more frequent wetting and drying cycles as opposed to more seasonal tropical forests with marked dry seasons that result in prolonged periods of unfavorable conditions for biological activity in the soil. However, Rubio and Detto (2017) reported diel patterns were most evident during the dry season at their seasonal tropical wet forest suggesting the processes responsible for the diel variability remain active during dry periods. In addition, although small in magnitude, their observed diel patterns were apparently driven by fluctuations in soil moisture rather than temperature (Rubio & Detto, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, tropical moist forests, such as our site, might exhibit more frequent wetting and drying cycles as opposed to more seasonal tropical forests with marked dry seasons that result in prolonged periods of unfavorable conditions for biological activity in the soil. However, Rubio and Detto (2017) reported diel patterns were most evident during the dry season at their seasonal tropical wet forest suggesting the processes responsible for the diel variability remain active during dry periods. In addition, although small in magnitude, their observed diel patterns were apparently driven by fluctuations in soil moisture rather than temperature (Rubio & Detto, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although small in magnitude, their observed diel patterns were apparently driven by fluctuations in soil moisture rather than temperature (Rubio & Detto, 2017). Other studies have found relationships with soil temperature similar to ours (Meir et al, 1996; Raich, 2017; Zanchi et al, 2014), although hysteresis was also evident suggesting other potential controls in addition to temperature on diel variation of soil respiration (Raich, 2017; Rubio & Detto, 2017; Vargas & Allen, 2008a; Zanchi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El clima de la isla es típico de un bosque tropical de tierras bajas, la temperatura promedio es de 27°C, la temporada lluviosa se extiende de mayo a diciembre y durante la temporada seca de mediados de diciembre a abril, los vientos alisios prevén tormentas convectivas de esta manera dictando los ritmos estacionales. La precipitación media anual es de 2642 (± 566) mm [27,31].…”
Section: Metodologíaunclassified
“…Las cámaras se instalan sobre estos collares que tienen un diámetro exterior de 20 cm y están ubicados en los vértices de un cuadrado de 20 × 20 m centrados radial a una torre microclimática, donde hay disponibilidad de red eléctrica; las mediciones de flujo de CO 2 se toman cada segundo durante 2 minutos después de que la cámara cierra. Se realiza una prepurga de 30 segundos y postpurga de 45 segundos para asegurar que el sistema se limpie entre cada medición [25,31].…”
Section: Flujo De Co 2 En Suelounclassified